Protest Against Social Injustice In Victor Hugo's Les Miserables (1862): A Marxist Criticism - Astuti, Erni Sri; , Dr. M. Thoyibi, M.S; , Mauly Halwat Hikmat, Ph. D (2014)
The aim of this research is to analyze how a protest against social injustice and its causes are expressed in the novelusing marxist criticism. This research is qualitative research. Technique of analyzing data is descriptive analysis. The techniques of collecting data are (1) Reading the novel of Les Miserables, (2)Identifying the topic of the novel, (3) Determining the character that will be analyzed, (4) Taking notes of important thing both of primary and secondary data source, (5) Reading some related books to find out the theory, and (6) Determining the issues of the novel. Based on the marxist criticism, it can be concluded that the writer of the novelprotests the social justice that happened in France in the mid of nineteenth century. Here the writer of the novel wants a revolution to get social justice in the society.